2014
DOI: 10.1098/rsif.2014.0752
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the fluid viscosity in tarsal hairy attachment systems of flies and beetles

Abstract: Wet adhesive systems of insects strongly rely for their function on the formation of capillary bridges with the substrate. Studies on the chemical composition and evaporation dynamics of tarsal secretions strongly suggest a difference in chemistry of secretion in beetles and flies, both possessing hairy attachment devices. This difference is assumed to influence the viscosity of the secretion. Here, we applied a microrheological technique, based on the immersion of nanometric beads in the collected tarsal foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Due to its polarity it can work as a bonding agent between two surfaces, and therefore have a substantial effect on adhesion [1821]. In insects the terminal contact elements of tenent setae are not dry, but rather wetted by a fluid secretion that is usually a micro-emulsion of water and oil, with varying fractions of substances [2231]. The mixture of both polar and non-polar substances presumably helps to wet both hydrophobic and hydrophilic surfaces building a fluid meniscus between the seta and the substrate to yield high capillary forces (wet adhesion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its polarity it can work as a bonding agent between two surfaces, and therefore have a substantial effect on adhesion [1821]. In insects the terminal contact elements of tenent setae are not dry, but rather wetted by a fluid secretion that is usually a micro-emulsion of water and oil, with varying fractions of substances [2231]. The mixture of both polar and non-polar substances presumably helps to wet both hydrophobic and hydrophilic surfaces building a fluid meniscus between the seta and the substrate to yield high capillary forces (wet adhesion).…”
Section: Introductionmentioning
confidence: 99%
“…The mixture of both polar and non-polar substances presumably helps to wet both hydrophobic and hydrophilic surfaces building a fluid meniscus between the seta and the substrate to yield high capillary forces (wet adhesion). The fluid can increase the contact area by filling minute cavities of micro- and nano-rough surfaces, where setae otherwise cannot adapt to, and prevents slipping of the foot due to its specific rheological properties [3135]. It was demonstrated that the presence of these secretions is crucial for the function of insect adhesive organs [6,36].…”
Section: Introductionmentioning
confidence: 99%
“…This finding provides insight into the role that viscous forces play in general insect adhesion: fly secretions are suited for shorter detachment times to escape from predators, while beetles sacrifice rapid mobility for increased adhesive force. [65] …”
Section: Chemical Adhesives For Stasis and Locomotionmentioning
confidence: 99%
“…In a comparative study of adhesive secretion viscosities, Peisker et al found that fly secretions (from Calliphora vicinia) have a much lower viscosity (10.9 mPa s) than secretions from beetles (Coccinella septempunctata, 21.8 mPa s). [65] Both of these insects have fibrous adhesive feet, so the difference can be attributed to the composition of the fluid. This finding provides insight into the role that viscous forces play in general insect adhesion: fly secretions are suited for shorter detachment times to escape from predators, while beetles sacrifice rapid mobility for increased adhesive force.…”
Section: Chemical Adhesives For Stasis and Locomotionmentioning
confidence: 99%
See 1 more Smart Citation